CHALLENGING FOR SEAGRASS MANAGEMENT IN INDONESIA - N adiarti; Etty Riani; Ita Djuwita; Sugeng Budiharsono; Ari Purbayanto; Harald Asmus (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Seagrasses, one of the important ecosystems in Indonesian coastal waters, have declined mostly due to a variety of multi-sector (i.e. ecology, socio-economy, technology and institution) anthropogenic disturbances. The decline and loss of seagrass meadows will have an effect not only on biodiversity and fisheries productivity within the ecosystems but also on the adjacent ecosystems (coral reef and mangrove forest), and even the effect will spread out far to the outside of the areas where seagrass grow.  Seagrass ecosystems management in Indonesia is urgently required as part of fisheries management. However, this concept has not been understood by most of Indonesian people, including some government officials. Consequently, the seagrass ecosystems are still marginalized in the coastal resource management practices in Indonesia. In order to sustain fisheries productivity, knowledge of impact scales of each seagrass-related multi-sector human activities are very important as one of basic requirements in designing an effective seagrass management.